Inflammation and immunity in the pathogenesis of hypoxic pulmonary hypertension - Ye, Yi; Xu, Qiying; Wuren, Tana (Frontiers in Immunology, 2023)
Hypoxic pulmonary hypertension (HPH) is a complicated vascular disorder characterised by a variety of diverse mechanisms and processes that eventually lead to elevated blood pressure in the pulmonary circulation. In recent years, evidence has grown indicating HPH is not simply a pathological syndrome characterized by hypoxia, but is instead a complex lesion of cellular metabolism, inflammation, and proliferation driven by the reprogramming of gene expression patterns. One of the key mechanisms behind HPH is hypoxia, which drives immune/inflammation to mediate complex vascular homeostasis that collaboratively controls vascular remodeling in the lungs. This is caused by the prolonged infiltration of immune cells and the increase of several pro-inflammatory factors, which ultimately leads to immune dysregulation. Hypoxia has been linked in preclinical studies to metabolic reprogramming, immunological dysregulation, and adverse pulmonary vascular remodeling. Many animal models have been developed to mimic HPH, however they have significant limitations. For example, many of these models do not accurately represent the human disease state and may not be suitable for testing new therapeutic strategies. The scientific understanding of hypoxic pulmonary hypertension is rapidly evolving, and recent efforts have focused on understanding the complex interplay between hypoxia, inflammation, and cellular metabolism in the development of this disease. Through continued research and the development of more sophisticated animal models, it is hoped that we will be able to deeper understand the underlying mechanisms of HPH and implement more effective therapies for this debilitating disease.